2009
DOI: 10.3201/eid1505.071618
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Dissemination of Methicillin-ResistantStaphylococcus aureus, Euregio Meuse-Rhin Region

Abstract: MRSA clones were associated with hospital-associated clonal complexes and with Panton-Valentine leukocidin–positive community-associated MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 39 publications
4
33
1
1
Order By: Relevance
“…Four MRSA isolates were associated with ST8-MRSA-IV (UK MRSA-2/-6), which was earlier found in Dutch hospitals and in multiple countries worldwide (9,50). Two MRSA isolates were associated with ST5-MRSA-II (New York/Japan clone), which was identified as the dominant MRSA in hospitals in New York and Japan (9) and was recently observed to be a dominant clone in the hospitals in The Netherlands as well (8). The other MRSA isolate was associated with ST228-MRSA-I (southern Germany clone) (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four MRSA isolates were associated with ST8-MRSA-IV (UK MRSA-2/-6), which was earlier found in Dutch hospitals and in multiple countries worldwide (9,50). Two MRSA isolates were associated with ST5-MRSA-II (New York/Japan clone), which was identified as the dominant MRSA in hospitals in New York and Japan (9) and was recently observed to be a dominant clone in the hospitals in The Netherlands as well (8). The other MRSA isolate was associated with ST228-MRSA-I (southern Germany clone) (9).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MLST CC8, CC15, and CC45 fluctuated over time. The change in prevalence might be due to import from abroad or from cross-border healthcare (8,52), but further studies to confirm this hypothesis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the spa sequence typing method, each identified repeat is associated to a code and a spa-type is deduced from the order of specific repeats. Although spa-typing has a lower discriminatory ability than PFGE [45,46], its cost-effectiveness, ease of use, speed, excellent reproducibility, appropriate in vivo and in vitro stability, standardised international nomenclature, high-throughput by using the StaphType software, and full portability of data via the Ridom database (http:// spaserver.ridom.de) makes this method the currently most useful instrument for characterising S. aureus isolates at the local, national and international levels [47][48][49][50][51][52]. Importantly, this approach ensures strict criteria for internal and external quality assurance of data submitted to the database that is curated by SeqNet.org [50,53].…”
Section: Staphylococcus Aureus Protein a Gene-typingmentioning
confidence: 99%
“…As published in 2009, the 'Rhine-Hesse' clone and the 'Berlin' clone are common in the Western German parts of the Euregio Meuse-Rhin (EMR) region, while -in addition to these clones -a higher clonal diversity was detected on the Dutch side. The predominant clonal complexes in the EMR region are CC5, CC8, CC30, and CC45 [29]. Another study identified the 'Barnim' clone as one of the predominant clones in the Dutch-German border area [30].…”
Section: Pfge For the Detection Of Changes In The Clonal Distributionmentioning
confidence: 99%